Combustion behaviour of plastic waste – A case study of PP, HDPE, PET, and mixed PES-EL - Mentes Dóra; Nagy Gábor; Szabó J. Tamás; Hornyák-Mester Enikő; Fiser Béla; Bela Fiser; Фішер Бейло; Viskolcz Béla; Póliska Csaba (Elsevier, 2023)
Abstract. Plastic production is skyrocketing due to convenience needs and thus, the amount of plastic waste is increasing. There are several different methods to handle plastic waste, within which waste-to-energy processes are viable options in certain settings. However, the combustion of materials is a complicated and complex process that can take place in a number of ways. When exposed to heat, different polymers behave differently (e.g. have different emission factors) and thus, not all types of plastic waste recommended to be handled through combustion. Therefore, it is vital to achieve a deeper understanding of these processes in order to decide on the end use of plastic materials. Four common types of polymers were studied: polypropylene (PP), high-density polyethylene (HDPE), polyethylene terephthalate (PET), and polyester-elastane (PES-EL) mixture. The combustion properties of the plastic materials were investigated. The experiments were carried out in a laboratory electric resistance tube furnace at two different temperatures (650 and 900 °C). The behavior of these mainly single-use plastic wastes and the changes in the concentrations of CO, CO2, NOx, and O2 flue gas components generated during combustion was studied to determine the quality of potential waste-to-energy processes.
Editorial board: https://www.sciencedirect.com/journal/journal-of-cleaner-production/about/editorial-board
Contents: https://www.sciencedirect.com/journal/journal-of-cleaner-production/vol/402/suppl/C
Keywords: Combustion behavior; Emission values; Flue gas components; Polymer combustion; Thermal analysis